Double-blind Evaluation of Verapamil, Propranolol, and Isosorbide Dinitrate against a Placebo in the Treatment of Angina Pectoris. Issue 5850 (17th February 1973) - Livesley, Brian; Catley, Patricia F.; Campbell, R. C.; Oram, Samuel
Abstract : In the treatment of angina pectoris a double-blind evaluation of verapamil (Cordilox) at two dose levels—namely, 80 mg thrice daily and 120 mg thrice daily—propranolol (Inderal) 100 mg thrice daily, and isosorbide dinitrate (Vascardin) 20 mg thrice daily has been made against a placebo. The assessment was based on relief from daily attacks of angina on effort and the response to a whole-body exercise test. We can find no statistically significant difference between the effects of verapamil (120 mg three times a day) and propranolol (100 mg three times a day) in the treatment of angina of effort. Both of these preparations are more effective than a placebo both in the reduction of daily attacks (P < 0·01) and in the prolongation of exercise test (P < 0·05). Isosorbide dinitrate (20 mg three times a day) appears to be no more effective than a placebo in the treatment of angina on effort, but 14 out of 32 patients experienced headache of such severity that even when the dose was reduced to 10 mg thrice daily this drug therapy had to be withdrawn. Both propranolol (100 mg three times a day) and verapamil (120 mg three times a day) had a significant lowering effect on the diastolic blood pressure as measured with the patient standing (P < 0·01).